2017
DOI: 10.1016/j.jcis.2016.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Solubility, structure, and morphology in the co-precipitation of cadmium and zinc with calcium-oxalate

Abstract: Calcium-oxalates (Ca-Ox), which are widely produced by microorganisms and plants, are ubiquitous and persistent biominerals in the biosphere. We investigated the potential trapping of two phytotoxic metals, cadmium (Cd) and zinc (Zn) by isomorphous substitution into the crystalline structure of Ca-Ox precipitated over a wide range of Cd/Ca or Zn/Ca ratio in solution. We employed atomic absorption spectroscopy, X-ray diffraction (XRD), and optical microscopy to evaluate our hypotheses that favorable solid-solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…17 The ion has been revealed to have a weak tendency for incorporation within calcium oxalate minerals with preferred formation of a zinc oxalate species. 18 One of the most important organic molecules studied in urolithiasis is citric acid 19,20 , due to the natural occurrence within urinary medium. Similar small compounds that are also present within the human body have also been studied, these being mainly amino acids, with varied results.…”
Section: Introductionmentioning
confidence: 99%
“…17 The ion has been revealed to have a weak tendency for incorporation within calcium oxalate minerals with preferred formation of a zinc oxalate species. 18 One of the most important organic molecules studied in urolithiasis is citric acid 19,20 , due to the natural occurrence within urinary medium. Similar small compounds that are also present within the human body have also been studied, these being mainly amino acids, with varied results.…”
Section: Introductionmentioning
confidence: 99%
“…The complex multicomponent composition of the crystallization medium (of urea and of other human physiological liquids), however, allows for the probability of such substitutions [22]. The probability of Cd-Ca substitutions in synthetic whewellite is proposed by McBride et al, 2017 [23].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has also observed a similar effect of Zn 2+ ions in favoring the weddellite structure over whewellite. 10 The CaOx monohydrate and CaOx dihydrate have fundamentally different structures: whewellite has a sheet structure formed by polyhedral layers of Ca polyhedra parallel to the (001) plane; the weddellite structure has channels formed from Ca polyhedral chains that contain zeolitic water. 25,26 Therefore, we propose that trace metal cations such as Pb 2+ can be accommodated more readily into the channel structure of weddellite relative to the layered whewellite.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…8 Trace metals such as zinc (Zn), cadmium (Cd), and Pb can be incorporated into Ca-oxalate (CaOx) during coprecipitation, defined as the simultaneous crystallization of two or more components from aqueous solution to form a single phase (solid solution) or multiple discrete phases. 9,10 The coprecipitation process in plant cells can selectively sequester trace metals into oxalate crystals to protect plants from metal toxicity. 11−13 For instance, it was found that Cd but not Zn was sequestered into CaOx crystals of the hyperaccumulator species, Gomphrena claussenii, 14 a result consistent with the greater tendency of Cd relative to Zn to substitute into structural positions of the CaOx mineral whewellite.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation